1991
DOI: 10.1111/j.1540-8159.1991.tb04040.x
|View full text |Cite
|
Sign up to set email alerts
|

The Right Ventricular Outflow Tract as an Alternative Permanent Pacing Site: Long‐Term Follow‐Up

Abstract: The long-term characteristics of the right ventricular outflow tract have been assessed as an alternative permanent pacing site to the right ventricular apex. Thirty-three consecutive patients requiring ventricular pacing were randomized to be paced from one of the two sites. Pacing was performed using a screw-in lead, and a programmable pacemaker was used to facilitate threshold testing. There was no significant difference in the lead positioning time or any acute implant measurement (e.g., threshold at 0.5 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(31 citation statements)
references
References 3 publications
0
28
1
2
Order By: Relevance
“…Excluding the study of Giudici et al, comprising 92 patients, the effect demonstrated in the meta-analysis was at the limit of significance [38]. The subgroups benefiting the most from septal RVOT pacing were patients with a lower cardiac output, patients for whom QRS narrowed with pacing and even patients with a low EF and associated coronary heart disease [39,40]. Although septal RVOT pacing is as reliable as RV pacing, numerous limitations were discussed in this meta-analysis, which do not allow the advantages of septal pacing to be categorically determined: the lack of standardization of the pacing site, as only 60% of catheters were actually placed in the infundibular septum in these studies; considerable variability in the evaluation criteria of the studies, with measurements based on isotopic EF, ultrasound, dP/dt or cardiac output; low patient numbers in each study; inclusion of both prospective and retrospective studies; largely insufficient follow-up; monocentric studies [15].…”
Section: What About Scientific Evidence In Favour Of Systematic Septamentioning
confidence: 97%
“…Excluding the study of Giudici et al, comprising 92 patients, the effect demonstrated in the meta-analysis was at the limit of significance [38]. The subgroups benefiting the most from septal RVOT pacing were patients with a lower cardiac output, patients for whom QRS narrowed with pacing and even patients with a low EF and associated coronary heart disease [39,40]. Although septal RVOT pacing is as reliable as RV pacing, numerous limitations were discussed in this meta-analysis, which do not allow the advantages of septal pacing to be categorically determined: the lack of standardization of the pacing site, as only 60% of catheters were actually placed in the infundibular septum in these studies; considerable variability in the evaluation criteria of the studies, with measurements based on isotopic EF, ultrasound, dP/dt or cardiac output; low patient numbers in each study; inclusion of both prospective and retrospective studies; largely insufficient follow-up; monocentric studies [15].…”
Section: What About Scientific Evidence In Favour Of Systematic Septamentioning
confidence: 97%
“…The relative value of each site is currently conjectural, as different investigators report either improvement or limited change in function after stimulation of either of these three locations [17][18][19][20]. This study is not intended to try to solve this dilemma, but rather to determine if such regional unipolar stimulation interferes with the natural sequence existing after supraventricular stimulation from either sinus rhythm or atrial pacing.…”
Section: Introductionmentioning
confidence: 94%
“…Since the first randomized trial in 1991 of Barin et al, who randomized 33 patients to RVA or RVOT pacing and showed comparable electrical performance and complication rate during followup, the RVOT area has paved the way for further clinical studies on non-apical ventricular pacing sites. 14 The design of our study was proposed in 1995, when there was growing interest in the RV selective pacing sites and very strong believe in the superiority of RVOT over RVA pacing. The first patients were randomized at the end of 1995 and the last ones in 1997.…”
Section: Discussionmentioning
confidence: 99%